Learning Strategies and Learning Motivation Related to SKI Learning Outcomes: Strategi Pembelajaran dan Motivasi Belajar Terkait Hasil Belajar SKI - Siti Chairun Nisyah; Wahyudin Nur Nasution; Solihah Titin Sumanti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Effective learning strategies and student motivation are critical to achieving optimal educational outcomes, especially in Islamic education. Specific Background: In Madrasah Ibtidaiyah, particularly in MI Al-Fajar Medan Deli, the teaching of Sejarah Kebudayaan Islam (SKI) is still dominated by conventional lecture methods, resulting in low student engagement and achievement. Knowledge Gap: Limited studies have examined the combined effect of learning strategies and motivation on SKI learning outcomes at the elementary Islamic education level. Aims: This study aims to investigate the influence of learning strategies (Project-Based Learning vs. Expository) and learning motivation on SKI achievement. Results: Using a 2x2 factorial experimental design with 40 students, findings reveal that Project-Based Learning (PjBL) significantly outperforms the expository method in improving SKI learning outcomes. Both high and low motivation groups benefit more from PjBL, and a significant interaction exists between learning strategy and motivation. Novelty: This study is the first to integratively analyze the simultaneous effects of teaching strategy and student motivation on SKI performance in MI Al-Fajar using real classroom data. Implications: The findings support the implementation of PjBL as a superior strategy, particularly when aligned with student motivation levels, to enhance Islamic cultural history learning in primary religious education settings.Highlight : Project-based learning strategies have been proven to significantly improve SKI learning outcomes. Student motivation affects learning success. There is an interaction between learning strategies and motivation in influencing learning outcomes. Keywords : Project-Based Learning, Learning Motivation, Learning Outcomes, Expository Strategies, SKI